XML for data management - Aiken, Peter; Allen, David (Amsterdam ; Boston : Elsevier/Morgan Kaufmann, 2004)
XML in Data Management is for IT managers and technical staff involved in the creation, administration, or maintenance of a data management infrastructure that includes XML. For most IT staff, XML is either just a buzzword that is ignored or a silver bullet to be used in every nook and cranny of their organization. The truth is in between the two. This book provides the guidance necessary for data managers to make measured decisions about XML within their organizations. Readers will understand the uses of XML, its component architecture, its strategic implications, and how these apply to data management. To view a sample chapter and read the Foreword by Thomas C. Redman, visit http://books.elsevier.com/mk/?isbn=0120455994 * Takes a data-centric view of XML. * Explains how, when, and why to apply XML to data management systems. * Covers XML component architecture, data engineering, frameworks, metadata, legacy systems, and more. * Discusses the various strengths and weaknesses of XML technologies in the context of organizational data management and integration.
Preface Foreword Chapter 1 -- XML and DM Basics Chapter 2 -- XML From the Builders Perspective: Using XML Technologies to Support DM Chapter 3 -- XML Component Architecture (as it relates to DM) Chapter 4 -- XML and Data Engineering Chapter 5 -- Making & Using XML: the technologist's perspective Chapter 6 -XML Frameworks Chapter 7 -- XML-Based Portal Technologies and Data Management Strategies Chapter 8 -- XML & DM focused on Enterprise Application Integration (EAI) Chapter 9 -- XML, DM & Reengineering Chapter 10: Networks of Networks, Metadata, and the Future Chapter 11 -- Expanded Data Management Scope References.
Includes bibliographical references and index.
Keywords: XML (Document markup language); Electronic data processing; Electronic books